JURIDICAL OVERVIEW OF USE OF BRANDS DERIVED FROM WELL-KNOWN FICTIONAL CHARACTERS (STUDY IN TANJUNGPINANG CITY) - Marnia Rani (Arena Hukum, 2022)
This paper discusses the regulation regarding the use of brands originating from fictional characters, both from famous comics and animation, which are registered or unregistered for use by other parties. This normative legal approach examines laws and regulations, legal doctrines, and legal documents relating to brands originating from fictional characters. The results show that the unauthorized use of Marks derived from a wll-known animation characters by other parties can be sued under Law Number 20 of 2016 concerning Marks and Geographical Indications, because they can mislead the public regarding the origin, quality, type, size, variety, the purpose of using goods and/or services. Meanwhile, since Article 83 does not stipulate that the unauthorized use of a mark by another party must be registered, the owner of a registered mark may file a lawsuit against the use of a mark originating from a well-known fictional character against another party even though the other party does not register it.